Anticipated Banking Panics - Gertler, Mark; Kiyotaki, Nobuhiro; Prestipino, Andrea (American Economic Review, 2016)
We develop a macroeconomic model with banking instability. Sunspot runs can arise that are harmful to the economy. However, whether a run equilibrium exists depends on fundamentals. In contrast to earlier work, the probability of a sunspot run is the outcome of rational forecast based on fundamentals. The model captures the movement from slow to fast runs that was a feature of the Great Recession: A weakening of banks' balance sheets increases the probability of a run, leading depositors to withdraw funds from banks. These slow runs have harmful effects on the economy and set the stage for fast runs.